Classroom assessment : enhancing the quality of teacher decision making - Anderson, Lorin W. (L. Erlbaum Associates, 2003)
The goal of this bk is to help practicing & prospective teachers gather better info and make better decisions. Unlike more conventional classrm bks, it balances material about assmnt w/material about dec making. This bk focus on the link betwen them.